Bisprimer--a program for the design of primers for bisulfite-based genomic sequencing of both plant and Mammalian DNA samples - Kovacova, Viera; Janousek, Bohuslav (The Journal of heredity, 2012)
Plants and animals differ in the sequence context of the methylated sites in DNA. Plants exhibit cytosine methylation in CG, CHG, and CHH sites, whereas CG methylation is the only form present in mammals (with an exception of the early embryonic development). This fact must be taken into account in the design of primers for bisulfite-based genomic sequencing because CHG and CHH sites can remain unmodified. Surprisingly, no user-friendly primer design program is publicly available that could be used to design primers in plants and to simultaneously check the properties of primers such as the potential for primer-dimer formation. For studies concentrating on particular DNA loci, the correct design of primers is crucial. The program, called BisPrimer, includes 2 different subprograms for the primer design, the first one for mammals and the second one for angiosperm plants. Each subprogram is divided into 2 variants. The first variant serves to design primers that preferentially bind to the bisulfite-modified primer-binding sites (C to U conversion). This type of primer preferentially amplifies the bisulfite-converted DNA strands. This feature can help to avoid problems connected with an incomplete bisulfite modification that can sometimes occur for technical reasons. The second variant is intended for the analysis of samples that are supposed to consist of a mixture of DNA molecules that have different levels of cytosine methylation (e.g., pollen DNA). In this case, the aim is to minimize the selection in favor of either less methylated or more methylated molecules.
Keywords: Sequence Analysis, DNA; Magnoliopsida; metylace DNA; DNA primery; DNA Methylation; Software; sekvenční analýza DNA; savci; design s pomocí počítače; Sulfites; software; Animals; DNA Primers; Computer-Aided Design; siřičitany; Mammals; zvířata